Penerapan Metode SAW Dalam Penentuan Penerima Beasiswa Yayasan - Sundari Retno Andani; S Sumarlin; Romulo P. Aritonang (LPPM STIKOM Tunas Bangsa, 2024)
One very effective way to avoid dropping out of school is by providing scholarships. In increasing the quantity of human resources in Indonesia, scholarships can be used as a solution. A university can also participate in improving human resources in Indonesia, namely through providing foundation scholarships. Foundation scholarships are scholarships whose funding comes from a university foundation. Foundation scholarships are given to students who excel and are economically disadvantaged. In determining foundation scholarship recipients, a decision support system (SPK) is needed to obtain more objective results based on the criteria used. The Simple Additive Weighting (SAW) method is one of the methods used in the decision making process. The SAW method is also called the weighted sum method, because the SAW method seeks a weighted sum of the performance ratings for each alternative for all attributes. The criteria used in this research are the Grade Point Average (GPA), parental income and number of dependents. Calculations using the SAW method will produce weight values, criteria, alternatives and the final result is a ranking of scholarship recipients as a recommendation for decision making.